Developing effective R&D models in higher education: Criteria and structured approaches - Huang, Xin; Gábor , András (Vezetéstudomány / Budapest Management Review, 2024)
This study provides a comprehensive framework for analysing and developing research and development (R&D) models in higher education. Despite the evolution of R&D management practices, there remains a lack of clearly defined models that ensure long-term flexibility and effective management within rapidly changing environments. Drawing on existing literature, this paper proposes criteria and structured approaches for higher education institutions (HEIs) to manage and facilitate R&D activities. By focusing on key dimensions such as mission alignment, research strategy, innovation strategy, and intellectual capital management, this study aims to offer practical guidelines to enhance the competitiveness and societal impact of HEIs. The goal is to move beyond general recommendations and provide a detailed criteria checklist to guide the development of effective R&D models.